2020
DOI: 10.1002/brb3.1770
|View full text |Cite
|
Sign up to set email alerts
|

The effects of poverty stereotype threat on inhibition ability in individuals from different income‐level families

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 56 publications
0
7
0
3
Order By: Relevance
“…However, results involving the P3 ERP do not suggest any systematic task-related effects on the relationship between SES and ERP amplitudes. Specifically, similar SES effects on the P3 are observed when attentional tasks of different modalities were used (Katus et al, 2020 ; Wang and Yang, 2020 ) and differences in SES effects on the P3 were found when tasks tapping similar processes are used (Ruberry et al, 2017 ; St. John et al, 2019 ). Overall, this systematic review is unable to establish with certainty whether there are effects of behavioral task differences on the SES-ERP relationship.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…However, results involving the P3 ERP do not suggest any systematic task-related effects on the relationship between SES and ERP amplitudes. Specifically, similar SES effects on the P3 are observed when attentional tasks of different modalities were used (Katus et al, 2020 ; Wang and Yang, 2020 ) and differences in SES effects on the P3 were found when tasks tapping similar processes are used (Ruberry et al, 2017 ; St. John et al, 2019 ). Overall, this systematic review is unable to establish with certainty whether there are effects of behavioral task differences on the SES-ERP relationship.…”
Section: Discussionmentioning
confidence: 87%
“…Two studies found no P3 amplitude difference between SES groups (Kishiyama et al, 2009 ; Ruberry et al, 2017 ) in samples of children. However, Wang and Yang ( 2020 ) found larger P3 amplitude and latency for high-SES compared to low-SES adult participants in a word-matching task. Katus et al ( 2020 ) compared 1–5 months old from a low-income country (Gambia) to a high-income country (UK).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…An alternative explanation for the observed variability lies in the quality of early stimulation and cognitive training provided to children within the home environment before exposure to the homogenizing influence of the academic context [ 85 88 ]. Cross-cultural studies propose that the variability in certain measures could stem from the modulating effect of environmental variables specific to a cultural context.…”
Section: Discussionmentioning
confidence: 99%